New approach of recycling vanadium‐bearing slags as a binder in high‐alumina refractory castables application - Mathilda Derensy; Thomas Zanin; Jan‐Felix Bleck; Thorsten Tonnesen; Jesus Gonzalez‐Julian (International Journal of Ceramic Engineering & Science)
Abstract Handling the massive quantities of by‐products from metallurgical processes has become a major concern in recent decades. Efforts to develop sustainable alternatives for these secondary resources are ongoing to achieve the transition to climate neutrality. This study has investigated the potential of employing vanadium‐bearing slag as a new value‐added binder in refractories, aiming to replace virgin raw materials. Two types of vanadium‐bearing slags from BOF, each containing <2 wt.% vanadium were studied. Low‐cement vanadium slag‐based castables were prepared by gradually substituting 0, 2.5, and 5 wt.% of the commercial calcium aluminate cements (Secar71 and CMA72) by the slags. The flow values of the mixes containing 5 wt.% of slag decrease significantly from about 90% to 30% after 30 min, showing poor ability to flow and thus are not considered as self‐flow castables. Castables containing 2.5 wt.% of slag present a cold crushing strength value, in the range of 71–116 MPa while values for castables containing 5 wt.% of slag fall into the range of 53–68 MPa due to the lower packing properties leading to higher porosity and reduce in strength. Similar observation was concluded for cold modulus of rupture. The micrographs of the samples containing both slag and cement show promising compatibility between the binder and aggregates after sintering at 1500°C. Overall, characteristics obtained with the samples containing slag show promising alternatives as a refractory lining.